Thermal and physicochemical characterization of seven argentine rice flours and starches - Iturriaga, Laura Beatriz (2004)
Differential scanning calorimetry (DSC) was used to evaluate phase transitions of rice flours and starches from seven new argentine genotypes in systems with different water content. Flours of high, medium and low T G (gelatinization temperature) were detected; ΔHG (total gelatinization enthalpy) showed two homogenous groups (8.1-9.2 and 10.1-10.4 mJ/mg). Amylose-lipid complex melting endotherm in waxy rice flours was observed despite the low amylose content. It is suggested that this complex could be originated in the longest amylopectin branches and extra granular complexing lipids. Differential behaviour in waxy genotypes was found with decrease of water content, probably due to the highest water absorption capacity of the AP (amylopectin). Genotypes with high (26.8-28.6 g/100 starch), medium (19.6-20.7 g/100 g starch) and low total amylose (TAM) content was found (1.3-2.1g/100 g starch). In using X-ray diffraction, the relative crystallinity in waxy genotypes was found to be higher (48%) than that corresponding to the non-waxy ones (37-40%). A linear correlation between gelatinization process cooperativity and TAM was found to exist but no between ΔHG and TG with crystallinity and TAM. Glass transitions (Tg) of gelatinized starch-water systems were also determined by DSC. Results indicated higher values (-5.0 to 6.3°C) for flours than for starches (-10°C).